Metodologi Penelitian Ekonomi Islam: Perlukah berbeda? - M. Husein Sawit (Universitas Islam Indonesia, 1998)
Islamic economics in Indonesia has been less developed rather than in other countries such as Malasysia and Pakistan. Even through, the mushrooming discussion about Islamic economics in many universities recently has been grateful. The article extends theories and models developed for doing research about Islamic economic.